Laparoendoscopic single‐site nephroureterectomy for upper urinary tract urothelial carcinoma: outcomes of an international multi‐institutional study of 101 patients. (7th March 2013) - Park, Sung Yul; Rha, Koon Ho; Autorino, Riccardo; Derweesh, Ithaar; Liastikos, Evangelos; Tsai, Yao Chou; Seo, Ill Young; Nagele, Ugo; Abdel‐Karim, Aly M.; Herrmann, Thomas; Han, Deok Hyun; Rais‐Bahrami, Soroush; et al.
Abstract : What's known on the subject? and What does the study add?: LESS‐NU may be an alternative minimally‐invasive treatment option for patients eligible to undergo laparoscopic surgery for upper urinary tract urothelial carcinoma. The true benefits of LESS‐NU remain to be determined and require randomized control trials in the future. Despite encouraging early findings, clinical trials still are warranted before this procedure is adopted widely, and longer follow‐up is needed to determine its oncological durability. Objective: To report a large multi‐institutional series of laparoendoscopic single‐site (LESS) nephroureterectomy (NU). Materials and Methods: Data on all cases of LESS‐NU performed between 2008 and 2012 at 15 institutions were retrospectively gathered. The main demographic data and perioperative outcomes were analysed. Results: The study included 101 patients whose mean (sd ) age was 66.4 (9.9) years and mean (sd ) body mass index was 24.8 (4) kg/m 2, and of whom 29.7% had undergone previous abdominal/pelvic surgery. The mean (sd ) operating time was 221.4 (73.7) min, estimated blood loss 231.7 (348.0) mL. A robot‐assisted LESS technique was applied in 25.7% of cases. An extra trocar was inserted in 28.7% of cases to complete the procedure. Conversion to open surgery was necessary in three cases (3.0%). There was no bladder cuff excision in 20.8% of cases, and excision was carried out using a variety of techniques in the remaining cases. Six intra‐operative complications occurred (5.9%). The mean (sd ) length of hospital stay was 6.3 (3.5) days. The overall postoperative complication rate was 10.0%, and most of the complications were low grade (Clavien grades 1 and 2). The mean tumour size was 3.1 (1.9) cm. Pathological staging was pTis in two patients, pTa in 12 patients, pT1 in 42 patients, pT2 in 20 patients, pT3 in 23 patients and pT4 in two patients. Pathological grade was high in 71 and low in 30 patients. At a mean follow‐up of 14 months, six patients (5.9%) had died. Disease recurrence (including distant and bladder recurrence) was detected in 22.8% of patients, with a mean time to recurrence of 11.5 months. Conclusions: This study reports the largest multi‐institutional experience of LESS‐NU to date. Peri‐operative outcomes mirror those of published standard laparoscopy series. Despite encouraging early findings, longer follow‐up is needed to determine the oncological efficacy of the procedure.